Geometric Regularity, Symmetry and the Perceived Beauty of Simple Shapes. (January 2018) - Friedenberg, Jay
Geometric regularity is introduced as a simplicity metric for understanding the esthetics of basic polygons. In Experiment 1, undergraduates rated the perceived beauty of triangles varying in geometric regularity defined by their side-length standard deviation. Each type of triangle was used: equilateral, isosceles, right, and scalene. Ratings increased with an increase in regularity and were highest for symmetric shapes. The results were replicated in a second experiment using each type of quadrilateral: square, rectangle, parallelogram, rhombus, kite, isosceles, and trapezoid. Although ratings in Experiment 2 also increased with regularity, symmetry did not perfectly predict ranked order of preference. Symmetry, partial symmetry, and familiarity are discussed as factors that can account for the results. On the basis of the shapes used in this study, we conclude that simplicity in the form of geometric regularity is usually but not always preferred.